Service-oriented agents for collaborative industrial automation and production systems - Mendes, João M. (2010)
Service-oriented Multi-Agent Systems (SoMAS) is an approach to combine the fundamental characteristics of service-oriented and multi-agent methods into a new platform for industrial automation. Several research works already targeted the connection of these technologies, presenting different perspectives in how and why to join them. This research focuses on available efforts and solutions in the area of SoMAS and explains the idea behind the service-oriented agents in industrial automation. A SoMAS system is mainly composed by shared resources in form of services and their providing/requesting agents. The paper also discusses the required engineering aspects of these systems, from the internal anatomy to the interaction patterns. Parameters of flexibility, reconfiguration, autonomy and reduced development efforts were considered and they should be the trademark of SoMAS. Aiming to illustrate the proposed approach, an example of service-oriented automation agents is given.